Blood Pressure Control and Teamwork - Yusimy Alejo Padrón (Universidad de las Ciencias Médicas de Cienfuegos, 2022)
The Pan American Health Organization, together with other institutions, has developed the HEARST Initiative (Hearts), in order to improve the control and quality of life of hypertensive patients. This project, parallel to similar ones that are being developed in other areas of the World Health Organization, is based on experiences that show that care in health teams brings benefits at various levels: it improves knowledge of the disease by patients, increases their adherence to treatment and determines a reduction in hospitalizations.